2007
DOI: 10.1038/nature05732
|View full text |Cite
|
Sign up to set email alerts
|

TRIM25 RING-finger E3 ubiquitin ligase is essential for RIG-I-mediated antiviral activity

Abstract: Retinoic-acid-inducible gene-I (RIG-I; also called DDX58) is a cytosolic viral RNA receptor that interacts with MAVS (also called VISA, IPS-1 or Cardif) to induce type I interferon-mediated host protective innate immunity against viral infection. Furthermore, members of the tripartite motif (TRIM) protein family, which contain a cluster of a RING-finger domain, a B box/coiled-coil domain and a SPRY domain, are involved in various cellular processes, including cell proliferation and antiviral activity. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

43
1,655
7
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,458 publications
(1,709 citation statements)
references
References 21 publications
43
1,655
7
4
Order By: Relevance
“…Proteins involved in type I IFN induction are found ubiquitinated for their functional regulation. It has been reported that TRIM25 [19] and Riplet/RNF135 [20] act as ubiquitin ligases to activate RIG-I for IFN-b induction in their different sites of RIG-I ubiquitination. Another ubiquitin ligase RNF125 polyubiquitinates RIG-I through Lys48, leading to degradation of RIG-I [21].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins involved in type I IFN induction are found ubiquitinated for their functional regulation. It has been reported that TRIM25 [19] and Riplet/RNF135 [20] act as ubiquitin ligases to activate RIG-I for IFN-b induction in their different sites of RIG-I ubiquitination. Another ubiquitin ligase RNF125 polyubiquitinates RIG-I through Lys48, leading to degradation of RIG-I [21].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM5 inhibits infection of HIV-1 and other retroviruses upon entry into the cell by engaging the viral capsid and inducing premature uncoating [21]. Moreover, it has been reported that interferon signaling and NF-B signaling are regulated by TRIM proteins including TRIM8, TRIM21, TRIM25, TRIM27, TRIM30 and TRIM56 [5,[22][23][24][25][26][27]. Recently, it has been reported that TRIM56 interacts with STING and targets it for lysine 63-linked ubiquitination, followed by induction of STING dimerization and activation of the IFN-promoter [27].…”
Section: Discussionmentioning
confidence: 99%
“…TRIM proteins are involved in a various biological processes [3,4]. TRIM25, also known as estrogen-responsive finger protein (EFP), induces type I IFN production and NF-B activity through the conjugation of a lysine 63-linked polyubiquitin chain to RIG-I [5]. Another study showed that TRIM25 also has an E3 ligase activity for ISG15 conjugation [6].…”
Section: Introductionmentioning
confidence: 99%
“…TRIM25 plays a crucial role in the anti‐viral response by ubiquitinating the N‐terminal caspase activation and recruitment domains (CARDs) of the cytosolic pattern recognition receptor RIG‐I. This event is critical to promote interaction with the adaptor protein MAVS and the subsequent activation of a signalling pathway leading to type 1 interferon production (Gack et al , 2007). TRIM32 has a broader cellular role and has been shown to regulate neuronal development, the stability of sarcomeric architecture and has more recently been reported to restrict influenza A virus (Shieh et al , 2011; Zhang et al , 2012; Fu et al , 2015).…”
Section: Introductionmentioning
confidence: 99%